The Bronchus First and Vessels Simultaneously Stapled Technique: A Safe and Simple Method for Video-Assisted Right Upper Lobe Lobectomy - Xu, Hao; Zhang, Linyou (The Thoracic and Cardiovascular Surgeon, 2019)
Objective Video-assisted thoracic surgery lobectomy is a minimally invasive procedure for major pulmonary resection. The purpose of this study was to present a novel approach with a thoracoscope in the right upper lobe and to compare different lobectomy methods at our institution.Methods We reviewed the medical records of patients who underwent a thoracoscopic right upper lobectomy for lung cancer between September 2015 and September 2016. We performed 128 thoracoscopic right upper lobectomies: group A (n = 50) was treated with the bronchus-first and vessels simultaneously stapled method and group B (n = 78) was treated with the conventional isolation–ligation method. Preoperative mediastinal staging and lymphadenectomy followed the National Comprehensive Cancer Network guidelines. The intra- and postoperative outcomes were recorded and statistically compared.Results All patients underwent successful thoracoscopic right upper lobectomies. No significant differences in mean intraoperative blood loss, massive hemorrhage (>500 mL), and postoperative complications were observed between the two groups (p < 0.05). The mean operative time of group A was less than that of group B (110.80 ± 34.74 versus 167.01 ± 48.38 minutes, p = 0.000). The mean duration of chest drainage in group A was 4.34 ± 2.06 days, which was shorter than that of group B (5.85 ± 3.13 days, p = 0.017). No significant differences were observed in the local recurrence and distant recurrence between the two groups during the postoperative follow-up.Conclusions Thoracoscopic right upper lobectomy with the lobectomy bronchus-first and vessels simultaneously stapled method is a safe and efficient procedure that leads to better recovery.
Keywords: thoracoscopy/VATS; lobotomy; lung cancer